Antibacterial and antibiofilm mechanisms of carbon dots: a review. Issue 4 (5th January 2023) - Yu, Meizhe; Li, Peili; Huang, Ruobing; Xu, Chunning; Zhang, Shiyin; Wang, Yanglei; Gong, Xuedong; Xing, Xiaodong
Abstract : This review provides a systematic overview of the complicated antibacterial and antibiofilm mechanisms of carbon dots. Abstract : Due to the increasing bacterial resistance to conventional antibiotics, developing safe and effective approaches to combat infections caused by bacteria and biofilms has become an urgent clinical problem. Recently, carbon dots (CDs) have received great attention as a promising alternative to conventional antimicrobial agents due to their excellent antimicrobial efficacy and biocompatibility. Although CDs have been widely used in the field of antibacterial applications, their antibacterial and antibiofilm mechanisms have not been systematically discussed. This review provides a systematic overview on the complicated mechanisms of antibacterial and antibiofilm CDs based on recent development.